PENGEMBANGAN HANDOUT DISERTAI SOAL-SOAL LATIHAN PADA MATERI PEWARISAN SIFAT UNTUK SMP/MTs - Elfina, Yuci - (Pendidikan Biologi, 2014)
At MTsN Lembah Gumanti Solok, the Student Worksheet and textbook were used as thesources of learning materials. Unfortunately, the materials presented were not totally approriate tothe learning goals and were not yet complete. Furthermore, not all students were able to get thebook at cost, and the book available were not sufficient. As a consequence, the students gotdifficulties to recall the learning materials at home. One of the materials regarded as difficult forthe students in class IX of Junior High School to the understood was the CharacteristicsInheritance. This topic required the studentsâ skill to count. The sample items and the exerciseswere hard to be undestood. This topic was commonly tested in the Nasional Examination. To dealwith this problem, a handout was developed. This reserch was designed to produce handoutaccompanied with exercises on the characteristics inheritance topic for the studens in class IX ofSMP/ MTs. This research was conducted at MTsN Lembah Gumanti in March of Academic Year2014/2015. This was a developmental research which applied 4-D model including defining phase,designing phase, and developing phase. The data collected was in the form of primay data thatconsisted of scores gotten from the validity questionnaire and practicality test administered to theteacher and the students. The data was analyzed descriptively by using percentage technique. Thehandout produced had been valid (89,1%) either in term of didactic, construction and technique.The handout had also been very practical according to the teacher (89,3%) and according to thestudents (89,6). Then, it was concluded that this research had produced a handout accompaniedwith exercise which had been valid and practical.